ANTIOXIDANT ACTIVITIES, TOTAL FLAVONOID, PHENOLIC, CAROTENOID OF VARIOUS SHELLS EXTRACTS FROM FOUR SPECIES OF LEGUMES - Fidrianny, Irda; Puspitasari, Nuraini; Singgih W, Marlia (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objectives. The objectives of this research were to study antioxidant capacity from various extracts of legumes shells using two methods of antioxidant testing which were DPPH (2.2-diphenyl-1-picrylhydrazyl) and FRAP (Ferric Reducing Antioxidant Power) and correlation of total flavonoid, phenolic and carotenoid content in various extracts of legumes shells with DPPH and FRAP antioxidant capacities. Methods. Extraction was performed by reflux using different polarity solvents. The extracts were vaporated using rotavapor. Antioxidant capacities using DPPH and FRAP assays, determination of total phenolic, flavonoid and carotenoid content Â were performed by spectrophotometry UV-visible and its correlation with DPPH and FRAP antioxidant capacities were analyzed by Pearson method.Â Results. TNH2 (ethyl acetate shells extract of peanut) had the highest DPPH scavenging capacity with IC50 0.595 mg/mL, while MRH2 (ethyl acetate shells extract of red kidney bean) had the highest Â FRAP capacity with EC50 294.781 mg/mL. TNH2 contained the highest total flavonoid (13.37 g QE/100 g), TNH3 (ethanolic shells extract of peanut) had the highest phenolic content (6.91 g GAE/100 g) and KDL2 (ethyl acetate shells extract of soybean) had the highest carotenoid 0.33 g BET/100 g. Conclusions. There were positively and high correlation between total phenolic and total flavonoid content in bogor peanut and peanut shells extracts with their antioxidant activity using DPPH assays. FRAP capacities in all of shells extracts had no linier result with DPPHÂ scavenging capacities. Â Keywords: Antioxidants, DPPH, FRAP, legumes shells, flavonoid, phenolic, carotenoidÂ